A Dual Load-Modulated Doherty Power Amplifier Design Method for Improving Power Back-Off Efficiency - Yi Jin; Zhijiang Dai; Xiongbo Ran; Changzhi Xu; Mingyu Li (Sensors, 2023)
In this paper, the load modulation process of a Doherty power amplifier (DPA) is analyzed to address the issue of why designed DPAs have a very low efficiency in the back-off state in some cases. A general formula of the real load modulation process is also given for analyzing the load modulation of a peak PA matching network. This provides a new perspective for improving the back-off efficiency of a DPA. To improve the power back-off efficiency of a DPA, a dual load-modulated DPA (D-DPA) design method is proposed. The core principle of the proposed design method is to control the load modulation process from the carrier PA to the peaking PA based on the design method of the traditional two-way DPA. The efficiency of the peaking PA in the back-off region is enhanced, thereby improving the efficiency in the entire back-off region of the DPA. Based on the proposed design method, a D-DPA operating at 2 GHz is designed and fabricated. The test results show that the saturated output power and gain are 43.7 dBm and 9.7 dB, respectively, while the efficiency at 6 dB output power back-off is 59.2%. The designed D-DPA eliminates the efficiency pit of the traditional two-way DPA in the output power back-off region.